2022
DOI: 10.2337/db21-0803
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-Dependent miR-125b Is a Negative Regulator of β-Cell Function

Abstract: Impaired pancreatic β-cell function and insulin secretion are hallmarks of type 2 diabetes. miRNAs are short, noncoding RNAs that silence gene expression vital for the development and function of β cells. We have previously shown that β cell–specific deletion of the important energy sensor AMP-activated protein kinase (AMPK) results in increased miR-125b-5p levels. Nevertheless, the function of this miRNA in β cells is unclear. We hypothesized that miR-125b-5p expression is regulated by glucose and that this m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 55 publications
2
10
0
Order By: Relevance
“…However, a smaller study was unable to detect any difference in circulating miR-16-5p (Hocaoglu et al 2019), but this could be due to the low number of included subjects. Moreover, miR-16-5p was also found to be significantly increased in the first trimester (Cao et al 2017, Sorensen et al 2021, 2022, which suggests that miR-16-5p could potentially be used as a diagnostic as well as a prognostic biomarker of GDM. This is emphasized by the finding that miR-16-5p in combination with miR-29a-3p and the also GDM-associated miR-134-5p forms a superior diagnostic measure compared with 2 h plasma glucose following an OGTT (Sorensen et al 2021), which is one of the recommended diagnostic measures of the IADPSG (International Association of Diabetes and Pregnancy Study Groups 2010).…”
Section: Figurementioning
confidence: 92%
See 2 more Smart Citations
“…However, a smaller study was unable to detect any difference in circulating miR-16-5p (Hocaoglu et al 2019), but this could be due to the low number of included subjects. Moreover, miR-16-5p was also found to be significantly increased in the first trimester (Cao et al 2017, Sorensen et al 2021, 2022, which suggests that miR-16-5p could potentially be used as a diagnostic as well as a prognostic biomarker of GDM. This is emphasized by the finding that miR-16-5p in combination with miR-29a-3p and the also GDM-associated miR-134-5p forms a superior diagnostic measure compared with 2 h plasma glucose following an OGTT (Sorensen et al 2021), which is one of the recommended diagnostic measures of the IADPSG (International Association of Diabetes and Pregnancy Study Groups 2010).…”
Section: Figurementioning
confidence: 92%
“…2). Only 33 different miRNA species were investigated in more than 1 original study, with miR-29a-3p and miR-16-5p being the most studied miRNAs, investigated in 6 (Zhao et al 2011, Wander et al 2017, Tagoma et al 2018, Gillet et al 2019, Martinez-Ibarra et al 2019, Sorensen et al 2021, 2022 and 6 (Zhu et al 2015, Cao et al 2017, Tagoma et al 2018, Hocaoglu et al 2019, Martinez-Ibarra et al 2019, Sorensen et al 2021, 2022 original studies, respectively. miR-223-3p (Wander et al 2017, Tagoma et al 2018, Yoffe et al 2019, Sorensen et al 2021), miR-330-3p (Martinez-Ibarra et al 2019, Pfeiffer et al 2020, Xiao et al 2020, Sorensen et al 2021) and miR-132-3p (Zhao et al 2011, Tagoma et al 2018, Gillet et al 2019 were each investigated in four studies, while miR-155-5p (Wander et al 2017, Tagoma et al 2018, Hocaoglu et al 2019), miR-210-3p (Wander et al 2017, Tagoma et al 2018, Gillet et al 2019), miR-19a/b-3p (Cao et al 2017, Stirm et al 2018, Tagoma et al 2018), miR-17-5p (Cao et al 2017, Lamadrid-Romero et al 2018, Tagoma et al 2018) and miR-125a/b-5p…”
Section: Small Rna Arraysmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the promoting effect of AMPK on GSIS has been recently reported. It has shown that β cell‐specific deletion of AMPK increases the levels of miR‐125b‐5p, which could subsequently impair GSIS in both MIN6 cells and human islets 136 . As well, silencing of the metal‐dependent protein phosphatase 1E (PPM1E), the most markedly downregulated protein phosphatase in T2DM patients’ islets, can promote GSIS through increasing the phosphorylation of CaMKII, AMPK, and ACC 137 .…”
Section: Signaling Pathways In T2dmmentioning
confidence: 99%
“…It has shown that β cell‐specific deletion of AMPK increases the levels of miR‐125b‐5p, which could subsequently impair GSIS in both MIN6 cells and human islets. 136 As well, silencing of the metal‐dependent protein phosphatase 1E (PPM1E), the most markedly downregulated protein phosphatase in T2DM patients’ islets, can promote GSIS through increasing the phosphorylation of CaMKII, AMPK, and ACC. 137 Altogether, these conflicting results warrant further investigations to provide more reliable information on the role of AMPK in T2DM and its clinical application.…”
Section: Signaling Pathways In T2dmmentioning
confidence: 99%